Cleaning Up: Portuguese Women's Fight for Labour Rights in Toronto - Miranda, Susana P.; Iacovetta, Franca (Between the Lines, 2023)
This fascinating book uncovers the little-known, surprisingly radical history of the Portuguese immigrant women who worked as night-time office cleaners and daytime “cleaning ladies” in postwar Toronto. Drawing on union records, newspapers, and interviews, feminist labour historians Susana P. Miranda and Franca Iacovetta piece together the lives of immigrant women who bucked convention by reshaping domestic labour and by leading union drives, striking for workers’ rights, and taking on corporate capital in the heart of Toronto’s financial district. Despite being sidelined within the labour movement and subjected to harsh working conditions in the commercial cleaning industry, the women forged critical alliances with local activists to shape picket-line culture and make an indelible mark on their communities. Richly detailed and engagingly written, Cleaning Up is an archival treasure about an undersung piece of working-class history in urban North America. --Publisher's description